Hermeneutics and memory in selected works by Willem Boshoff - Tryon, Denzil Jordan (Rhodes University, Faculty of Humanities, Department of Fine Art, 2007)
From Introduction: Willem Boshoff was born in Vereeniging, South Africa, in 1951. The son of a carpenter, Boshoff developed an early interest in art. Although never taught formally by his father, he nevertheless acquired a knowledge of the craft of carpentry, a skill which he continues to utilize in much of his art-making today. Boshoff studied at the Johannesburg College of Art, and obtained a Master's Diploma in Technology in Fine Art in 1984. He taught at that institution for twelve years, becoming a full-time art practitioner in 1996. He produced some significant works prior to and during the time of his teaching tenure, including his KykAfrikaans visual poetry in 1979-1980, Bangboek between 1977-1986, and the researching and writing of the Dictionary of Perplexing English in 1986 (ending in 1999). In this study I will discuss Willem Boshoff's careful employment of language and materials, througb which he propagates his "study of ignorance" (Williamson and Jamal 1996:148). I will investigate two major works by Boshoff, namely The Writing in the Sand and The Blind Alphabet in Chapters 1 and 2 respectively. Both of these installations are concerned fundamentally with the subversion of power relationships and elitism. As I will show, both works offer an opportunity to investigate their objectives in relation to discourses surrounding language and hermeneutics. My study includes a third chapter, in which I discuss my own work entitled The Bread of the Presence in relation to Boshoff's own methodologies. As will be demonstrated with particular reference to The Blind Alphabet and my own work, a discussion of memory proves to be of some relevance within this dialogue.
Keywords: Boshoff, Willem, 1951- -- Hermeneutics; Memory in art; Art, Modern -- 20th century -- South Africa; Installations (Art) -- South Africa